2012
DOI: 10.1080/07391102.2012.689695
|View full text |Cite
|
Sign up to set email alerts
|

The relation of the X-ray B-factor to protein dynamics: insights from recent dynamic solid-state NMR data

Abstract: In addressing the potential use of B-factors derived from X-ray scattering data of proteins for the understanding the (functional) dynamics of proteins, we present a comparison of B-factors of five different proteins (SH3 domain, Crh, GB1, ubiquitin and thioredoxin) with data from recent solid-state nuclear magnetic resonance experiments reflecting true (rotational) dynamics on well-defined timescales. Apart from trivial correlations involving mobile loop regions and chain termini, we find no significant corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…Generally, R 2 values for all resolved residues (loops and β‐sheet) are higher compared with the values obtained for resolved β‐sheet residues alone. This result supports the conclusions stated above from previous studies48, 62 that no explicit correlation exists between order parameters and X‐ray B‐factors. We find that Cα carbons exhibit the lowest correlation (R 2 of 0.08 and 0.02 for all residues and β‐sheet residues, respectively), whereas Cβ carbons have the highest R 2 values (R 2 of 0.33 and 0.11).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Generally, R 2 values for all resolved residues (loops and β‐sheet) are higher compared with the values obtained for resolved β‐sheet residues alone. This result supports the conclusions stated above from previous studies48, 62 that no explicit correlation exists between order parameters and X‐ray B‐factors. We find that Cα carbons exhibit the lowest correlation (R 2 of 0.08 and 0.02 for all residues and β‐sheet residues, respectively), whereas Cβ carbons have the highest R 2 values (R 2 of 0.33 and 0.11).…”
Section: Resultssupporting
confidence: 93%
“…It is less established that B‐factors and NMR parameters are correlated. In fact, in a recent paper by Reichert et al 62. it has been shown that for various NMR dynamic timescale measurements, extracted for a variety of proteins studied by MAS NMR spectroscopy, there is a poor correlation between B‐factor values and NMR dynamic measurements of backbone nitrogen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Although B-factors are impacted by model error and lattice imperfections and report more on static disorder within the crystalline environment as opposed to motions in solution (33,34), we reasoned that an analysis of a large number of pMHC complexes would allow some of these limitations to be circumvented.…”
Section: Peptides Alter the Hydrogen/deuterium Exchange Behavior Of Tmentioning
confidence: 99%
“…[8,14] Such conformational switching is the functionally most relevant dynamic mode of GPCRs. [10,15] A second dynamic mode involves local fluctuations in the backbone and the side chain in thermodynamic equilibrium. [10,15] These can occur as local fluctuations as well as correlated motions of entire secondary structure units.…”
Section: Introductionmentioning
confidence: 99%